2018
DOI: 10.1016/j.jadohealth.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Chosen Name Use Is Linked to Reduced Depressive Symptoms, Suicidal Ideation, and Suicidal Behavior Among Transgender Youth

Abstract: For transgender youth who choose a name different from the one given at birth, use of their chosen name in multiple contexts affirms their gender identity and reduces mental health risks known to be high in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
179
2
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 351 publications
(213 citation statements)
references
References 7 publications
6
179
2
7
Order By: Relevance
“…They already feel wrong in their bodies, many have comorbidities as a result of their dysphoria, including body dysmorphic disorder, depression, and significant anxiety. This is consistent with current research [3,4]. As nurses, we can do better, especially in the hospital.…”
supporting
confidence: 92%
“…They already feel wrong in their bodies, many have comorbidities as a result of their dysphoria, including body dysmorphic disorder, depression, and significant anxiety. This is consistent with current research [3,4]. As nurses, we can do better, especially in the hospital.…”
supporting
confidence: 92%
“…The risks and benefits of medical gender affirmation should also be considered in a social context. Recent data showed that transgender youth who were able to use their chosen name (rather than name assigned at birth) reported fewer depressive symptoms and less suicidal ideation and behaviour, suggesting that psychosocial burdens may also unsurprisingly be alleviated by social, non-medical interventions 26. Alternatively, for example, the persistence of a prepubescent body habitus due to puberty suppression has been linked to decreased social inclusion for transgender youth whose physical development is asynchronous to their cisgender peers 5 9…”
Section: Medical Gender Affirmation: Risks and Benefits In Minorsmentioning
confidence: 99%
“…8 Using the person's chosen name is associated with lower depression, suicidal ideation, and suicidal behavior. 9 In their everyday lives, trans people often share the experience of social exclusion, lack of (legal) gender recognition, discrimination, and stigmatization, similar to members of other sexual or gender minorities. Rejection, nonaffirmation, and victimization are strongly related to suicidal ideation through experiences of internalized transphobia and negative expectations.…”
Section: Evidencementioning
confidence: 99%